Case Study Antarctica: Up Against the Ice Barrier: Antarctic Tourism Operators Prepare for the Polar Shipping Code - Julia Jabour (2017)
The ‘cryosphere’ is the world of ice. It includes Arctic and Antarctic sea and land ice, which scientists claim provides the most ‘visible signatures of climate change’ (Vaughan et al., 2013, p. 319). When sea ice forms and expands, its extent can be seen and measured from space, and when it contracts the chlorophyll in ice-edge nutrient blooms that sustain cold-water life can also be seen from space. When land ice melts, that, too, is obvious – with massive icebergs calving off friable ice sheets and ice shelves at the water’s edge and soaking the ocean with dense, cold, fresh water. These occurrences can be both sporadic and annual; they can be unpredictable, inconsistent and regionally asymmetrical; and occasionally they can defy developing trends. Understanding the ice regimes of the polar regions is a difficult task in these warming environments. This, together with the prospect of increased shipping activity in iceless polar waters, has prompted – in part – the development of the International Maritime Organization’s (IMO) International Code for Ships Operating in Polar Waters (hereafter, the Polar Code), which came into effect in January 2017.